First trans-neptunian object in polar resonance with neptune - Morais, M. H.M. [UNESP]; Namouni, F. (Oxford University Press (OUP), 2017)
Capture in mean motion resonance has been observed in the Solar system for small objects with prograde as well as retrograde orbits of moderate inclinations. However, no example of an object with a nearly polar orbit was known to be in resonance with a planet. In this Letter, we report that the nearly-polar trans-Neptunian object (471325), nicknamed Niku, is in a 7:9 resonance with Neptune, with a mean lifetime in resonance of 16 ± 11 million years. While entrance and exit in the 7:9 resonance is caused by close encounters with Neptune, the resonant configuration provides a temporary protection mechanism against disruptive close encounters with this planet. The other nearly polar trans-Neptunian objects do not seem to be in resonance with the planets with the possible exception of 2008 KV42, also known as Drac, that has a small chance of being in the 8:13 resonance with Neptune.
Keywords: Celestial mechanics; Comets: general; Kuiper belt: general; Minor planets, asteroids: general; Oort Cloud